Corrigendum: PD-1/PD-L1 immune checkpoint therapy demonstrates favorable safety profile in patients with autoimmune and cholestatic liver disease - Kocheise, Lorenz; Piseddu, Ignazio; Vonderlin, Joscha; Tjwa, Eric T; Buescher, Gustav; Meunier, Lucy; Goeggelmann, Pia; Fianchi, Francesca; Dumortier, Jérôme; Barciela, Mar Riveiro; Gevers, Tom J G; Beretta-Piccoli, Benedetta Terziroli; et al. (Frontiers in immunology, 2024)
[This corrects the article DOI: 10.3389/fimmu.2023.1326078.].
Keywords: autoimmune hepatitis (AIH); primary biliary cholangitis (PBC); autoimmune liver diseases (AILD); autoimmune disease (AID); immune related adverse effects (irAEs); primary sclerosing cholangites (PSC); immune checkpoint inhibitors (ICI); PD-1/PD-L1 immune checkpoint inhibitors